Possible involvement of invariant natural killer T cells and mucosal-associated invariant T cells in a murine model of titanium allergy. Issue 1 (January 2018) - Kumagai, Kenichi; Matsubara, Ryota; Nakasone, Yasunari; Shigematsu, Hiroaki; Kitaura, Kazutaka; Suzuki, Satsuki; Haneji, Kuniaki; Hamada, Yoshiki; Suzuki, Ryuji
Abstract: Objective: Titanium alloy has long been regarded as a biocompatible material, and is widely used for implants in medicine and dentistry. Titanium is thought to be a potential cause of metal allergy, however, accumulating T cells during development of titanium allergy have been poorly characterized because basic research based on a suitable animal model has not been performed. This study aimed to investigate the skewing of the T-cell receptor repertoire and cytokine profiles of accumulated T cells in inflamed skin during titanium allergy. Methods: A novel model of titanium allergy was induced by two sensitizations by injection of TiCl3 plus lipopolysaccharide solution into the mouse groin followed by two challenges with TiCl3 into the footpad. Cytokine expression profiles, T cell phenotypes, and T-cell receptor repertoire were determined in the titanium-induced allergic footpads. Results: Significant swelling and pathological features, such as spongiosis of the dermis, were histologically evident at 7 days after challenge in mice with titanium allergy. Characterization of the TCR repertoire revealed the presence of the TRAV10/TRAJ18 clonotype, indicative of natural killer T cells, and TRAV1/TRAJ33, associated with mucosal-associated invariant T (MAIT) cells in the inflamed skin of both the irritant and allergic mice models. Conclusions: Our murine model of titanium-induced hypersensitivity shows that NKT cells and MAIT cells participate in titanium allergy.